Cemented Bipolar Hemiarthroplasty Vsproximal Femoral Nails:A Prospective Comparative Outcome Analysisin Unstable Elderly Intertrochanteric Fractures (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: intertrochanteric; fracture; hemiarthroplasty; bipolar; PFN; elderly; osteoporosis